Modern Approach to Ureteral Stones - Geert G. Tailly (The Scientific World Journal)
Urolithiasis is a very common affliction of mankind. In western countries incidence is increasing steadily. An increasing proportion of patients are presenting with ureteral stones, of which renal colic most often is the first complaint and the most common reason for an emergency visit to a urologist. Proper imaging strategy is of paramount importance in the diagnosis of acute flank pain and in the subsequent therapy planning once a ureteral stone is diagnosed. Renal colic during pregnancy poses specific problems, both in imaging and therapy. Apart from the adequate treatment of renal colic, modern therapy of those ureteral calculi that will not pass spontaneously will consist of a judicious combination of ESWL (extracorporeal shock wave lithotripsy), endourology, and laparoscopy. Open surgery should only be reserved for limited and very specific indications. Although beyond the scope of this article, metaphylaxis should take an important role in the follow-up of stone patients in general.